THE ROLE OF EDUCATIONAL SERVICES IN THE SOCIO-ECONOMIC DEVELOPMENT OF THE COUNTRY - Yulduz Pirnazarovna Urunbayeva; Temirova Shalola Erkinovna (Ecominds Press, 2026)
This article discusses the fact that educational services are a unique intangible asset and their specific characteristics, the specifics of economic relations in the market for these services. In addition, the article presents theoretical and scientific data on the high level of monopolization in educational services as a result of the large share of state ownership in the means of production.
Keywords: Educational services, education, personality, outlook, succession, Social relations.